Children's distal forearm fractures: a population-based epidemiology study of 4, 316 fractures. (6th June 2022) - Korup, Lærke R.; Larsen, Peter; Nanthan, Kumanan R.; Arildsen, Marie; Warming, Nikolaj; Sørensen, Søren; Rahbek, Ole; Elsoe, Rasmus
Abstract : Aims: The aim of this study was to report a complete overview of both incidence, fracture distribution, mode of injury, and patient baseline demographics of paediatric distal forearm fractures to identify age of risk and types of activities leading to injury. Methods: Population-based cohort study with manual review of radiographs and charts. The primary outcome measure was incidence of paediatric distal forearm fractures. The study was based on an average at-risk population of 116, 950. A total number of 4, 316 patients sustained a distal forearm fracture in the study period. Females accounted for 1, 910 of the fractures (44%) and males accounted for 2, 406 (56%). Results: The overall incidence of paediatric distal forearm fractures was 738.1/100, 000 persons/year (95% confidence interval (CI) 706/100, 000 to 770/100, 000). Female incidences peaked with an incidence of 1, 578.3/100, 000 persons/year at age ten years. Male incidence peaked at age 13 years, with an incidence of 1, 704.3/100, 000 persons/year. The most common fracture type was a greenstick fracture to the radius (48%), and the most common modes of injury were sports and falls from ≤ 1 m. A small year-to-year variation was reported during the five-year study period, but without any trends. Conclusion: Results show that paediatric distal forearm fractures are very common throughout childhood in both sexes, with almost 2% of males aged 13 years sustaining a forearm fracture each year. Cite this article: Bone Jt Open 2022;3(6):448–454.